BANDING IN AORTIC STENT-GRAFT FIXATION IN EVAR - Utíkal, Petr; Köcher, Martin; Bachleda, Petr; Dráč, Petr; Černá, Marie; Buriánková, Eva (Biomedical papers, 2004)
The authors describe the method of surgical aortic banding for better stent-graft fixation in cases of problematic aortic neck in the endovascular infrarenal aneurysms repair.
Keywords: Aorta/Aneurysms/Repair/Endovascular/Stent-graft/Fixation/Endoleak/Migration/Complications